Developing and Implementing Hospital Quality Systems for Efficient Healthcare Operations Management - Divya Deepthi Panditi, Ms.; M.K. Badri Narayanan, Dr. (International Journal of Engineering and Technology, 2018)
Quality Management Systems becoming more important and plays a major role in current Public and Private healthcare sector to achieve clinical excellence. Effective quality management systems results in modification, expansion and the modernization of healthcare services.Efficient healthcare operations of hospitals is also the major concern for the management team which involves multiple departments, numerous activities, interlinked processes and the effective usage of resources. Implementation of hospital quality systems will streamlines the processes of both clinical and nonclinical departments which results in efficient healthcare operations management.The public and private healthcare sector is gradually changing due to the growing influence of the patient association, increased competition in the market and the necessity of the healthcare service delivery in a more effective and efficient manner. Especially in public healthcare sector, change management is the biggest task. It is very important to the employees of public healthcare sector to accept for change management which helps to improve their skills and to achieve service excellence.This paper provides a simple and clear description to the healthcare quality and operations team about how to develop and implement quality systems in hospitals which leads to efficient healthcare operations management.Â